A CONTRIBUTION TO THE DISTRIBUTION KNOWLEDGE OF THE SOME NEOPHYTES IN THE FLORA OF SARAJEVO CANTON ANDHERZEGOVINA-NERETVA CANTON (Works of the Faculty of Agriculture and Food Sciences University of Sarajevo, 2026)
The aim of this paper was to present new data on the presence of a selected neophytes. In accordance with the aim, three-year field research was carried out (2019 – 2022) in Sarajevo Canton (KS) and Herzegovina-Neretva Canton (HNK). The conducted research is significant because for many neophytes there is no systematized way of examining their presence and distribution, which can be very significant in adequate control strategies. Following species were examined: Euphorbia maculata L., Euphorbia nutans L., Datura stramonium L., Ambrosia artemisiifolia L. and Helianthus tuberosus L. For each locality, a number of parameters were recorded, such as: altitude, latitude and longitude, land type and phytocoenological affiliation. Altitude, latitude and longitude were determined with GPS "MagellaneXplorist 500". Numerous literature data and herbarium collections of the National Museum of Bosnia and Herzegovina (B&H) were examined, in order to determine whether all of the localities are new for the researched species. The largest number of new localities was recorded for the species Ambrosia artemisiifolia (6), followed by Euphorbia maculata (4), Datura stramonium (3), Helianthus tuberosus (2) and Euphorbia nutans (1). Most of the investigated plant species are found in the anthropogenic order Chenopodietalia.